Design And Implementation Of Accounting Information System In Toko Batam Expo - Serly Serly; Delnecca Delnecca (Universitas Internasional Batam, 2023)
This community service program aims to design and implement an accounting recording system in one of the Micro, Small, and Medium Enterprises (MSMEs) which is still constrained by the process of recording transactions and accounting reporting. The object of this program is the Toko Batam Expo which is engaged in furniture. Toko Batam Expo has been operating for 10 years but does not have an accurate and detailed recording system. The unavailability of accurate financial information related to their business makes it difficult for store owners to make decisions about developing their business. Methods of data collection using interviews, observation, design and implementation. The result of community service is the creation of a simple and easily accessible accounting system to meet the needs and conditions of the Toko Batam Expo. The system is designed using Microsoft Access where business owners can enter transactions through forms and can easily access financial reports including statements of financial position and income statements. For further research, it is recommended to be able to understand the characteristics of the research object well so as to be able to produce innovations and solutions that are more useful for other MSMEs.